Analysis of Physics Learning Outcomes of Class XI Students of SMAN 1 Maros in the Implementation of the Merdeka Curriculum - Fathur Rakhman Lukman; Usman; Mutahharah Hasyim (Physics Education, 2026)
This study aims to determine the physics learning outcomes of class XI students at senior high school 1 Maros on the topic of momentum and impulse. This study used descriptive quantitative method with a sample of 92 students in class XI with an interest in physics subjects. The instrument used was cognitive test instrument in the form of multiple choice questions. The results of data analysis classified learning outcomes in five categories, with 15.22% of learners reaching the very high category, 56.52% of participants in the high category, 18.48% in the medium category, 9.78% in the low category, and 0% in the very low category, with an average score of 16.17. Based on the results of research and data analysis, it can be concluded that the physics learning outcomes of class XI students at senior high school 1 Maros are in the high category.